Informe de nuevas especies fungicas en casimon (Pothomorphe peltata (L.) Miq.) en Cuba - Veitia, M.=700 1 Lopez, D.; Lopez, M.O.
(Es, En)
Ilus., 8 ref.
Keywords: HONGOS; ESPECIES NUEVAS; REGISTRO; CUBA; CAISIMON; POTHOMORPHE PELTATA